Simulation study on the material stress distribution respect to different angle of ECAP - Kamaruddin, Akmalia Shahira; Katimon, Mohd Nizam (2022)
This research study focused on the influence of channel angle towards stress distribution of material aluminium alloy 5083. The size of the grain is related to the mechanical properties of material. Equal channel angular pressing (ECAP) is a process to produce ultrafine-grained, a method for deforming materials in such a way that a strong mechanical properties material is generated while the dimensions of the work piece remained unchanged. Die channel angle is one of the parameter in ECAP. To design a die channel angle, it is important to understand the effect of it with material stress distribution. A simulation using ABAQUS CAE has been carried out at channel angle 90°, 110°, and 130° to understand the effect die channel angle toward stress distribution. The die channel angle is designed differently to see the effect of stress distribution when the work piece passed through the channel angle. The grain structure was assessed at the point where the die's channels angle intersected. The analysis obtained in this study shows the result of the influence of die channel angle towards stress distribution. It is understood that the channel angle affects the mechanical behavior as the angle decrease from 110° to 90°, the higher the stress occur at the channel angle.